LD mapping of maternally and non-maternally derived alleles and atopy in FcepsilonRI-beta. - Traherne, J; Hill, MR; Hysi, P; D'Amato, M; Broxholme, J; Mott, R; Moffatt, M; Cookson, W (2003)
Polymorphisms in the beta chain of the high affinity receptor for IgE (Fc epsilon RI-beta, MS4A2) are consistently associated with traits underlying asthma and atopy (immunoglobulin E-mediated allergy). However, the causal variants and haplotypes underlying disease have not yet been identified. Maternal effects, with association confined to maternally derived alleles, have been shown in some studies but not in others. We have therefore extended the known sequence and systematically detected polymorphisms across an 18.1 Kb genomic region that includes Fc epsilon RI-beta. Association testing in two panels of subjects showed the presence of single-nucleotide polymorphisms (SNPs) affecting prick skin tests and specific IgE responses in several clusters. Stepwise analyses indicated that the clusters represent independent effects. Interferon regulatory factor 2 (IRF-2) sites were altered by significantly associated SNPs in two regions. Strong association to maternally derived alleles was seen in one panel of subjects and not in the other. Maternal and non-maternally derived associations tended to share the same SNP clusters, but associations were stronger in the presence of maternal effects. Two regions of increased CpG concentration were identified in Fc epsilon RI-beta. One of these approximated a SNP cluster that showed strong association and maternal effects, providing a potential substrate for epigenetic effects.